GAMBARAN PENGETAHUAN, SIKAP, DAN PERILAKU MASYARAKAT TENTANG UPAYA PENCEGAHAN PENYAKIT DBD DI KELURAHAN KENTENG KECAMATAN MADUKARA KABUPATEN BANJARNEGARA TAHUN 2021 - Joko Malis (Unit Penelitian dan Pengabdian Masyarakat, Politeknik Banjarnegara, 2021)
Dengue Hemorrhagic Fever (DHF) is a disease caused by the dengue virus which is transmitted from person to person through the bite of the Aedes sp. The results of the preliminary survey found that in recent years the incidence of dengue fever has always occurred repeatedly in Kenteng Village. The purpose of this study was to describe the knowledge, attitudes, and behavior of the community regarding efforts to prevent dengue fever in Kenteng Village, Madukara Sub-District, Banjarnegara District in 2021. This study is an observational study, namely research that observes the influence between the independent variable and the dependent variable through testing. hypotheses that have been formulated. The research design used was cross sectional. The sample population is the family head of Kenteng Village, Madukara Sub-District, Banjarnegara Dsitrict. The number of samples after being determined by the Slovin formula is 74 respondents who will be selected by simple random sampling. The results showed that the majority of respondents were in the age group of 20-40 years (47.3%), most of the highest education levels were elementary school graduates (43.3%), most of the types of work were housewives or did not work (39.2%), most of the monthly income is still below the UMK (60.8%). Most of the respondents had a sufficient level of knowledge about dengue prevention (82.4%). Most of the respondents have a good attitude about the prevention of DHF (78.4%). Most of the respondents have a positive attitude about the prevention of DHF (93.2%). Knowledge of attitudes and behavior of most of the respondents was classified as good. It is hoped that there will be socialization / counseling about the importance of preventing DHF to increase knowledge about DHF for the community.